Bronchiectasis morphology and hemoptysis recurrence after bronchial artery embolization: a cohort study using inverse probability of treatment weighting - Duan, Yuxin; Sui, Weifan; Cai, Zefeng; Xia, Yimao; Li, Jianyun; Fu, Jianhua (Frontiers in Medicine, 2025)
BackgroundHemoptysis is a serious and often life-threatening symptom associated with various pulmonary conditions, with bronchiectasis being a common cause. Bronchial artery embolization (BAE) is an effective intervention for managing hemoptysis, yet recurrence rates remain high. Several studies have identified general risk factors for recurrence. However, the role of bronchiectasis subtypes in predicting long-term outcomes after BAE has not been thoroughly explored.ObjectiveTo assess the association between cystic bronchiectasis and the risk of hemoptysis recurrence following BAE, compared to non-cystic bronchiectasis subtypes.MethodsThis retrospective cohort study included 168 adults treated with BAE for hemoptysis due to bronchiectasis from January 2017 to April 2022. Bronchiectasis was classified as cystic or non-cystic according to the Reid morphological criteria. Baseline differences between groups were adjusted using inverse probability of treatment weighting (IPTW).ResultsPatients with cystic bronchiectasis exhibited a significantly higher recurrence risk than those with non-cystic bronchiectasis before and after IPTW adjustment (HR = 2.62; 95% CI, 1.42–4.82; p < 0.001). This association remained consistent across subgroup analyses stratified by age, sex, and various comorbidities, with cystic bronchiectasis consistently showing a higher recurrence risk.ConclusionsCystic bronchiectasis is a significant independent predictor of hemoptysis recurrence following BAE. These findings suggest bronchiectasis morphology, especially cystic changes, should be recognized as an important prognostic factor when selecting candidates for BAE and planning long-term management.